x → − ∞ lim ( 2 x + 4 x 2 + 3 x − 2 ) = ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Relevant wiki: Limits by Rationalization
Let x = − t
L = t → ∞ lim ( − 2 t + 2 t 1 − 4 t 3 − 2 t 2 1 ) = t → ∞ lim ( − 2 t + 2 t ( 1 − 8 t 3 − 4 t 2 1 ) )
L = − 0 . 7 5
L = t → ∞ lim 4 t 2 − 3 t − 2 + 2 t 4 t 2 − 3 t − 2 − 4 t 2 = t → ∞ lim 2 1 − 4 t 3 − 2 t 2 1 + 2 − 3 − t 2
L = − 0 . 7 5
Nice solution
Take 4x^2 common from square root and take square root as -2x as x is negative and then use binomial approximation to get
2x-2x(1+3/8x) = -3/4
did same , minus bhul gya yaar :P
Problem Loading...
Note Loading...
Set Loading...
Relevant wiki: Limits by conjugates
L = x → − ∞ lim ( 2 x + 4 x 2 + 3 x − 2 ) = x → − ∞ lim ( 2 x + 4 x 2 + 3 x − 2 ) × 4 x 2 + 3 x − 2 − 2 x 4 x 2 + 3 x − 2 − 2 x = x → − ∞ lim 4 x 2 + 3 x − 2 − 2 x 4 x 2 + 3 x − 2 − 4 x 2 = x → − ∞ lim 4 x 2 + 3 x − 2 − 2 x 3 x − 2 = u → ∞ lim 4 u 2 − 3 u − 2 + 2 u − 3 u − 2 = u → ∞ lim ( 4 u 2 − 3 u − 2 + 2 u − 3 u − 4 u 2 − 3 u − 2 + 2 u 2 ) = u → ∞ lim ⎝ ⎛ 4 − u 3 − u 2 2 + 2 − 3 − 0 ⎠ ⎞ = − 4 3 = − 0 . 7 5 Let u = − x Divide first term up and down by u